Working hours and job sharing in the EU and USA are Europeans lazy? Or Americans crazy? - Boeri, Tito.; Burda, Michael C.; Kramarz, Francis (Oxford : Oxford University Press, 2008)
Why do Europeans work so little compared to Americans? Can they be induced to work more without reducing labour productivity? This volume explores these questions and more in order to understand the changing nature of the hours worked in the USA and EU, as well as the effects of policies that impose working hour restrictions.
Selected conference papers.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Hours of labor -- European Union countries -- Congresses; Hours of labor -- United States -- Congresses; Labor productivity -- European Union countries -- Congresses; Labor productivity -- United States -- Congresses; Job sharing -- European Union countries -- Congresses; Job sharing -- United States -- Congresses